USULAN PENERAPAN METODE SIX SIGMA UNTUK MENINGKATKAN KUALITAS KLONGSONG (STUDI KASUS INDUSTRI SENJATA) - Gunawan Pakki; Rudy Soenoko; Purnomo Budi Santoso (Badan Penerbit Jurnal, Faculty of Engineering, Universitas Brawijaya, 2014)
Weapons Industy has the greatest asset in the production of klongsong with various varians meet the basic needs of military and public supplies, klongsong types 6 mm. Improving in quality does is not mean to increase the amount of labor or replace the old machine with a new one but rather to maximize the performance of the production system elements. This research is proposed to reduce the reject rate klongsong 6 mm process and to to determine the factors that influence the defective product. Six Sigma concept is used to discover and to reduce the factors that cause disability and error so as to improve the quality to wards zero failure rate. Six Sigma framework is known as Define, Measure, Analyse, Improve, and Control (DMAIC). In Define phase of DMAIC is to define CTQ (Critical-To-Quality) through interviews with company management. In the Measure phase of DMAIC level of product quality (products klongsong 6 mm casing) is measured. In Analysis phase of DMAIC the causes of defects is analyzed through Ishikawa diagram. In Improve phase of DMAIC the preparation of the proposed improvements is based on is based on prioritization using FMEA. The results of the analysis of the application of Six Sigma in production klongsong in average was 4.69 with DPMO 695.429.